Onomastic phraseological units in media discourse: typology and communicative roles - Niyazmetova , Shakhsanam (The Lingua Spectrum, 2025)
This study explores the classification and functional roles of onomastic phraseological units (OPUs) in modern media discourse. OPUs, which incorporate proper names, play a crucial role in enhancing expressiveness, shaping public opinion, and reinforcing cultural narratives. The research categorizes OPUs based on their structural, semantic, and functional characteristics while analyzing their impact in journalistic, advertising, and political texts. The findings highlight their rhetorical, persuasive, and cognitive significance in media communication. Furthermore, the paper delves into historical aspects of OPUs and their evolution in different linguistic and cultural contexts.